The Christmas swap [large type] - Carlson, Melody (Thorndike Press large print Christian fiction, 2020)
"All Emma Daley wants this holiday season is a white Christmas. But the young teacher and struggling musician sure can't find that in sunny Arizona. Luckily, there's someone living in a perfect mountain home in the Colorado Rockies looking to make a vacation trade. West Prescott is an in-demand songwriter and talented musician who put his own singing career on hold to write songs for celebrity acts to perform. When his mother convinces him to do a vacation trade for Christmas, he never imagined one of the houseguests would be so sweet--or so strikingly pretty. Naturally, he decides to stick around, and to get better acquainted, he poses as the caretaker of his own house. But when Emma's friend Gillian discovers his true identity and sets her sights on him, things get...messy." --